Cell senescence alters responses of porcine trabecular meshwork cells to shear stress - Du, Ruotian; Li, Dongyan; Zhu, Meng; Zheng, Lisha; Ren, Keli; Han, Dong; Li, Long; Ji, Jing; Fan, Yubo (Frontiers in Cell and Developmental Biology, 2022)
Mechanical microenvironment and cellular senescence of trabecular meshwork cells (TMCs) are suspected to play a vital role in primary open-angle glaucoma pathogenesis. However, central questions remain about the effect of shear stress on TMCs and how aging affects this process. We have investigated the effect of shear stress on the biomechanical properties and extracellular matrix regulation of normal and senescent TMCs. We found a more significant promotion of F-action formation, a more obvious realignment of F-actin fibers, and a more remarkable increase in the stiffness of normal cells in response to the shear stress, in comparison with that of senescent cells. Further, as compared to normal cells, senescent cells show a reduced extracellular matrix turnover after shear stress stimulation, which might be attributed to the different phosphorylation levels of the extracellular signal-regulated kinase. Our results suggest that TMCs are able to sense and respond to the shear stress and cellular senescence undermines the mechanobiological response, which may lead to progressive failure of cellular TM function with age.